Model Pendidikan Islam Berbasis Budaya Masyarakat Studi Kasus di Pondok Pesantren Miftahul Huda Malang - khoirul wafa wafa (Universitas Nahdlatul Ulama Blitar, 2022)
Education is a strategic vehicle to deliver bright, skillful and high technology young generation of the nation who can build Indonesia to be a internationally competitive and respectable nation. It shapes children’s physic such as brain and soul such as spirit and also trains their skill based on their potency in order to make them to have a tawadhu’ and noble character.Therefore, it is important to have an Islamic education model integrated in Islamic boarding school. As explained in the background of the study, to obtain an accurate data the researcher employs instruments such as (1) in-depth interview using interview technique; (2) unstructure interview in order to make the interview itself less rigid and more; (3) participant observation. It is done in order to develop understanding on the background and to find out the feeling of the subject; (4) documentation, to explore data which is not obtained through interview and observation. The study employs a qualitative approach and case study research.